Health‐related quality of life outcomes in PARAGON‐HF. (9th December 2022) - Chandra, Alvin; Polanczyk, Carisi A.; Claggett, Brian L.; Vaduganathan, Muthiah; Packer, Milton; Lefkowitz, Martin P.; Rouleau, Jean L.; Liu, Jiankang; Shi, Victor C.; Schwende, Heike; Zile, Michael R.; Desai, Akshay S.; et al.
Abstract: Aims: Heart failure (HF) is associated with poor health‐related quality of life (HRQL). Patients with HF with preserved ejection fraction (HFpEF) have similar HRQL impairment as those with reduced ejection fraction. This study describes the impact of sacubitril/valsartan on HRQL in patients with HFpEF enrolled in the PARAGON‐HF trial. Methods and results: Patients completed the Kansas City Cardiomyopathy Questionnaire (KCCQ) and EuroQol (EQ‐5D) at randomization, 4, 8 months, and annually thereafter. Changes in HRQL scores were evaluated using repeated measures models adjusted for treatment, baseline values and region. The pre‐specified principal efficacy assessment was at 8 months at which time patients randomized to sacubitril/valsartan had borderline higher KCCQ clinical summary score (CSS) with least squares mean (LSM) adjusted difference of 1.0 (95% confidence interval [CI] 0.0, 2.1; p  = 0.051). Including all visits up to 36 months, the LSM difference in KCCQ‐CSS favoured sacubitril/valsartan with average adjusted difference of 1.1 (95% CI 0.1, 2.0; p  = 0.034). Patients treated with sacubitril/valsartan had greater odds of clinically meaningful improvement (≥5‐point increase) in KCCQ‐CSS (odds ratio 1.31; 95% CI 1.06, 1.61) at 8 months. At 8 months, there was no significant difference in the EQ visual analogue scale between the treatment arms, but sacubitril/valsartan was associated with higher EQ‐5D utility score (US‐based) with LSM adjusted difference of 0.01 (95% CI 0.00, 0.02; p  = 0.019). Conclusion: Compared with valsartan, sacubitril/valsartan had a borderline benefit on KCCQ‐CSS at 8 months in patients with HFpEF. This benefit became more significant when data from all visits up to 36 months were included. This modest overall benefit was also supported by greater odds of patients reporting a clinically meaningful improvement in HRQL with sacubitril/valsartan. Abstract : Health‐related quality of life (HRQL) outcomes in PARAGON‐HF. CI, confidence interval; HFpEF, heart failure with preserved ejection fraction; KCCQ, Kansas City Cardiomyopathy Questionnaire; LSM, least squares mean; LVEF, left ventricular ejection fraction; NYHA, New York Heart Association; SE, standard error.